Reconstruction of the lateral defect of the lower lip by a combination of two advancement flaps - Marijan Kovačić (Hrvatski liječnički zbor, 2021)
Introduction: The functional and esthetic result of the reconstruction of the lower lip after the removal of the tumor depends on the correct choice of surgical technique. Given the fact that their number is great, the choice is not easy. Patients and methods: In this study, the authors included five patients who underwent reconstruction of a lower lip defect with a combination of two lobes, an elastic vermilion lobe, and an island V-Y mental sliding lobe. All patients had squamous cell carcinoma of the lateral part of the lower lip ≥ 2cm (T2). An elastic vermilion flap popularized by Goldstein, and the well-known island V-Y advancement mental flap introduced into the surgical practice by Bayamicli et al. were used. A very good esthetic and functional result was achieved. The formed lip has an appropriate natural look, quality volume, symmetry , matching width and height. Conclusion: This combination of two established flaps is a serious alternative to other surgical techniques in the reconstruction of a lower lip defect that is not suitable for direct remediation, primary closure. The surgical technique of flaps formation is not difficult, can be performed under local anesthesia, and does not require long surgical time.